The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3390/coatings10010082
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Coatings Based on Titanium Dioxide Nanosolson Polyester Fibre Materials

Abstract: In this paper, we show that functionalization of fibrous materials through coating formation is hindered by the need to preserve the capillary-porous system of the fabric and its drapability. Additionally, such coatings must be resistant to abrasion and washing. We consider ways of solving these problems by analysing the formation of a stable coating based on photoactive titanium dioxide on a polyester fibre material as an example. The purpose of such coatings is to destroy coloured organic contaminants when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…On the contrary, fiber webs with random surface roughness and extreme porosity showed much higher bacteria adhesion ( Figure 3 b and Figure 4 c) [ 31 , 32 , 34 ]. Similar to the preceding, Bajpai et al [ 14 ] demonstrated that fabrics with a rough surface, such as cotton, had a great bacterial adherence. Puddles and random-sized pores that are accessible from the web surface would allow strong attachment of bacteria.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…On the contrary, fiber webs with random surface roughness and extreme porosity showed much higher bacteria adhesion ( Figure 3 b and Figure 4 c) [ 31 , 32 , 34 ]. Similar to the preceding, Bajpai et al [ 14 ] demonstrated that fabrics with a rough surface, such as cotton, had a great bacterial adherence. Puddles and random-sized pores that are accessible from the web surface would allow strong attachment of bacteria.…”
Section: Resultsmentioning
confidence: 55%
“…For example, as a preventative measure to bacterial growth on textiles, various antimicrobial treatments such as quaternary ammonium compounds, triclosan, and chitosan have been incorporated into fibers [ 9 ]; however, those materials often fail to kill every organism effectively. Biocidal nanoparticles including silver [ 10 , 11 , 12 ], copper [ 12 , 13 ], titanium dioxide [ 14 , 15 , 16 ], and zinc oxide [ 17 , 18 , 19 ] are also used, where silver is particularly effective at interfering with bacterial metabolism. However, the adverse effect of those reactive species on human cells is still obscure, and the environmental and toxicological [ 20 , 21 , 22 ] concerns about using nanoparticles still remain.…”
Section: Introductionmentioning
confidence: 99%
“…37 Prorokova et al have investigated the use of TiO 2 particulate coatings to create self-cleaning fibers. 38,39 As TiO 2 nanoparticles absorb light in the presence of water vapor, they form reactive oxygen species (ROS) which degrade any unwanted compounds forming within a material or on its surface through a radical mechanism. In plastics, ROS scavengers often prevent further degradation of the polymeric matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium dioxide (TiO 2 ) is a common whitening agent in foods (e.g., Twinkies) and widespread additive in both food packaging (due to its biocidal properties) 34,35 and commodity plastics, where TiO 2 nanoparticles prevent excessive bleaching and/or yellowing of plastics such as poly(ethylene) 36 and poly(vinyl chloride) 37 . Prorokova et al have investigated the use of TiO 2 particulate coatings to create self‐cleaning fibers 38,39 . As TiO 2 nanoparticles absorb light in the presence of water vapor, they form reactive oxygen species (ROS) which degrade any unwanted compounds forming within a material or on its surface through a radical mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The photocatalytic properties of TiO 2 can be used when TiO 2 is irradiated with light, and the bandgap will produce electron and hole pairs which cause a redox reaction on the surface of TiO 2 . As a result, electrons will move from the valence band to the conduction band so that electron and hole pairs will form on the photocatalyst surface [6], coats the polyester fabric TiO 2 , which has high sedimentation stability. As a result, a very thin layer is formed on the surface of each polyester fabric fibre.…”
mentioning
confidence: 99%